HLA-G Haplotypes Are Differentially Associated with Asthmatic Features - Ribeyre, Camille (Front Immunol, 2018)
Human leukocyte antigen (HLA)-G, a HLA class Ib molecule, interacts with receptors on lymphocytes such as T cells, B cells, and natural killer cells to influence immune responses. Unlike classical HLA molecules, HLA-G expression is not found on all somatic cells, but restricted to tissue sites, including human bronchial epithelium cells (HBEC). Individual variation in HLA-G expression is linked to its genetic polymorphism and has been associated with many pathological situations such as asthma, which is characterized by epithelium abnormalities and inflammatory cell activation. Studies reported both higher and equivalent soluble HLA-G (sHLA-G) expression in different cohorts of asthmatic patients. In particular, we recently described impaired local expression of HLA-G and abnormal profiles for alternatively spliced isoforms in HBEC from asthmatic patients. sHLA-G dosage is challenging because of its many levels of polymorphism (dimerization, association with β2-microglobulin, and alternative splicing), thus many clinical studies focused on HLA-G single-nucleotide polymorphisms as predictive biomarkers, but few analyzed HLA-G haplotypes. Here, we aimed to characterize HLA-G haplotypes and describe their association with asthmatic clinical features and sHLA-G peripheral expression and to describe variations in transcription factor (TF) binding sites and alternative splicing sites. HLA-G haplotypes were differentially distributed in 330 healthy and 580 asthmatic individuals. Furthermore, HLA-G haplotypes were associated with asthmatic clinical features showed. However, we did not confirm an association between sHLA-G and genetic, biological, or clinical parameters. HLA-G haplotypes were phylogenetically split into distinct groups, with each group displaying particular variations in TF binding or RNA splicing sites that could reflect differential HLA-G qualitative or quantitative expression, with tissue-dependent specificities. Our results, based on a multicenter cohort, thus support the pertinence of HLA-G haplotypes as predictive genetic markers for asthma.